A formação do professor em exercício e o desenvolvimento criativo e reflexivo: Estudo de Caso com Professores do Instituto de Magistério Primário da Matola - Moçambique - Ussene, Camilo Ibraimo (2006)
The purpose of this study is to analyse the teacher training process of trainees that are at same time working as teachers at Instituto do Magistério Primário da Matola in Mozambique and contribute to the development of creative and reflective attitudes for better teaching practices. The object of the research is the development of creative and reflective posture of the trainees that are working as teachers in Mozambique While developing creative postures during the training of these professionals, it is on the belief that they will conditions to apply them in their future practice and consequently create and develop creative reflective attitudes in their students. The study is a proposal of qualitative and descriptive research including what is known as case study. It s an exploratory research for the fact tat its main purpose is to develop, clarify and modify concepts and ideas for formulation of better approaches for the development of subsequent activities. For that reason the exploratory research represents the first stage of study in order to familiarize the researcher with the subject to be studied. The results of the research show that the creativity and refle ctivity are not present in the Teaching and Learning process as it can be seen from the les sons observed at IMAP as well as at Escola Primária do Jardim, specifically regarding the trainers and trainees observed. The connection between theory and practice occurs the without the awareness of real relationship between these two aspects If the teachers training programs include reflection to action, this relation will develop a creative and reflective teacher